1999
DOI: 10.1038/sj.sc.3100873
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical aspects of sensory substitution and of neurotransmission-related reorganization in spinal cord injury

Abstract: Spinal cord rehabilitation has progressed enormously since World War II, and persons with spinal cord injuries now have long life expectancies. Research has recently concentrated on improvement of the quality of life, and on neural mechanisms of recovery. This article will explore some aspects of both of these areas. In the ®rst section, the potential applications of sensory substitution systems for such functions as sex sensation and sensation from feet and from robotic hands will be examined. In the second s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Another even more spectacular example of how with artificial input the CNS may adapt and recover function is provided by the great success of the bionic ear developed by Graeme Clark et al 75 Similar but less outstanding results have been achieved for the substitution of vision using tactile stimulation. 76 Another reason for optimism is the well-known ability of the CNS to respond to external and internal stimuli by changing its synaptic connections by means of plasticity. The relearning of skills and language after stroke or head injury is due to this phenomenon, best seen in the young in whom language centers may even be relocated to another topographic site in the brain.…”
Section: The Futurementioning
confidence: 99%
“…Another even more spectacular example of how with artificial input the CNS may adapt and recover function is provided by the great success of the bionic ear developed by Graeme Clark et al 75 Similar but less outstanding results have been achieved for the substitution of vision using tactile stimulation. 76 Another reason for optimism is the well-known ability of the CNS to respond to external and internal stimuli by changing its synaptic connections by means of plasticity. The relearning of skills and language after stroke or head injury is due to this phenomenon, best seen in the young in whom language centers may even be relocated to another topographic site in the brain.…”
Section: The Futurementioning
confidence: 99%
“…For neuroscientists, the relationship between sensory-motor loops and physical integration appear obvious. Several studies have demonstrated this: research on the subject of the physical integration of vibrotactile devices used to substitute visual loss [33]; work on the development of the sense of orientation through long-term wearing of a "compass-belt" which provides constant vibrotactile information on the direction of North [34], or the "rubber hand" experiments in which the combination of sensory signals (visual and tactile) generate the sensation that a rubber hand is a part of the subject's own body [35].…”
Section: Integrity and Integrationmentioning
confidence: 98%
“…A video camera signal was converted into a tactile image and projected onto the blind subject's back. In [7] Bach-y-Rita reviews the theoretical aspects and many applications from the beginning to 1999. In the past decade further results were published: Bach-y-Rita, Kaczmarek and Tyler introduced the tongue based man machine interface [8].…”
Section: Concept Of Contrast-based Feedback Techniquementioning
confidence: 99%